Preventive effects of the novel antimicrobial peptide Nal-P-113 in a rat Periodontitis model by limiting the growth of Porphyromonas gingivalis and modulating IL-1β and TNF-α production - Hong-yan Wang; Li Lin; Wei Fu; Hui-Yuan Yu; Ning Yu; Li-si Tan; Jya-wei Cheng; Ya-ping Pan (BMC, 2017)
Abstract Background P-113 (AKRHHGYKRKFH-NH2) is a 12-amino-acid histidine-rich peptide derived from histatin 5 that is highly degradable in high salt concentrations and biological fluids such as serum, plasma and saliva. Nal-P-113, a novel antimicrobial peptide whose histidine residues are replaced by the bulky amino acids β-naphthylalanine, causes the antimicrobial peptide to retain its bactericidal activity even in physiological environments. This study evaluated the effect of the novel antimicrobial peptide Nal-P-113 in a rat periodontitis model and the mechanisms of action of Nal-P-113 for suppressing periodontitis. Methods Periodontitis was induced in mandibular first molars in rats receiving a ligature and infected with Porphyromonas gingivalis. Animals were randomly divided into six groups: a, P. gingivalis W83 alone; b, P. gingivalis W83 with 6.25 μg/mL of Nal-P-113; c, P. gingivalis W83 with 25 μg/mL of Nal-P-113; d, P. gingivalis W83 with 100 μg/mL of Nal-P-113; e, P. gingivalis W83 with 400 μg/mL of Nal-P-113; and f, control without P. gingivalis W83 or Nal-P-113. Morphometric analysis was used to evaluate alveolar bone loss. Microbiological assessment of the presence of Porphyromonas gingivalis and total bacteria was performed using absolute quantitative real-time PCR and scanning electron microscopy. Gingival tissue was collected for western blot and immunohistochemical assays of IL-1β and TNF-α levels. Results Alveolar bone loss was inhibited by 100 μg/mL or 400 μg/mL of Nal-P-113 compared to the control group (P < 0.05). Lower amounts of P. gingivalis and total bacteria were found in groups d and e compared with group a (P < 0.05). A decrease in the levels of IL-1β and TNF-α was detected in group d and group e compared to the control group (P < 0.05). The amount of P. gingivalis was positively correlated with IL-1β and TNF-α expression in periodontal tissue (P < 0.05). Conclusions Nal-P-113 exhibited protective effects on Porphyromonas gingivalis-induced periodontitis in rats by limiting the amount of bacteria and modulating IL-1β and TNF-α production. The use of Nal-P-113 in vivo might serve as a beneficial preventive or therapeutic approach for periodontitis.